P286 Correlations of functional multi-nuclear MR imaging indices with pulmonary function tests in the assessment of idiopathic pulmonary fibrosis. (12th November 2015) - Weatherley, ND; Stewart, NJ; Marshall, H; Collier, G; Hart, K; Horn, F; Norquay, G; Whyte, MK; Bianchi, S; Wild, JM
Abstract : Disease progression in idiopathic pulmonary fibrosis (IPF) is variable and unpredictable. Declining forced vital capacity (FVC) and transfer factor (TLCO) of 10% and 15% respectively are common markers of deterioration, but may be insufficiently sensitive to prognosticate and rely on serial measurements. Echocardiography provides screening for pulmonary artery hypertension (PAH), but is insensitive to pulmonary haemodynamic change before PAH is already apparent. Recently established Magnetic Resonance Imaging (MRI) techniques may provide insight into evaluating IPF. Greater septal thickness as measured by hyperpolarised xenon in patients with IPF compared with with healthy volunteers was previously demonstrated. 1 Here, we investigate the correlation between MRI indices, including hyperpolarised gas ventilation and gadolinium-enhanced perfusion, with pulmonary function parameters in a pilot cohort of subjects with IPF. Six subjects with IPF were recruited. T1 mapping was performed in all subjects. Imaging sequences following inhalation of hyperpolarised 3-Helium was used to calculate estimates for ventilated volume percentage (VV%) and coefficient of variation of ventilation (CoV). Dynamic contrast-enhanced lung perfusion MRI was performed for pulmonary haemodynamic assessment All subjects underwent pulmonary function testing (PFTs). VV% strongly correlated with transfer coefficient (KCO) with R = 0.955; p = 0.003, but also FEV (forced vital capacity)/FVC ratio. CoV is a measure of regional ventilation heterogeneity and trended to correlation with transfer factor TLCO (R = -0.775; p = 0.108). Time to peak (TTP) of the gadolinium perfusion signal showed negative correlation with FVC (R = -0.909 with p < 0.05) and trended to a negative correlation with TLCO (R = -0.766, p = 0.131). All p values two-tailed. TTP correlation with PFT values suggests that changes in pulmonary haemodynamics may be detectable at an early stage of the disease process. VV% and helium mapping may provide information about regional airways ventilation in IPF. MRI based assessments could prove useful in assessing different aspects of lung structure-function for use in future research and potentially in clinical assessment of patients with IPF. Sequential imaging with concurrent PFT and echocardiography would help to further assess the applicability of evolving MRI techniques. Reference: 1 Stewart NJ, et al . Magn Reson Med . 2015;74 (1):196–207